Circular spectropolarimetric sensing of chiral photosystems in decaying leaves. (March 2017) - Patty, C.H. Lucas; Visser, Luuk J.J.; Ariese, Freek; Buma, Wybren Jan; Sparks, William B.; van Spanning, Rob J.M.; Röling, Wilfred F.M.; Snik, Frans
Abstract: Circular polarization spectroscopy has proven to be an indispensable tool in photosynthesis research and (bio)molecular research in general. Oxygenic photosystems typically display an asymmetric Cotton effect around the chlorophyll absorbance maximum with a signal ≤ 1 % . In vegetation, these signals are the direct result of the chirality of the supramolecular aggregates. The circular polarization is thus directly influenced by the composition and architecture of the photosynthetic macrodomains, and is thereby linked to photosynthetic functioning. Although ordinarily measured only on a molecular level, we have developed a new spectropolarimetric instrument, TreePol, that allows for both laboratory and in-the-field measurements. Through spectral multiplexing, TreePol is capable of fast measurements with a sensitivity of ∼ 1 * 10 − 4 and is therefore suitable of non-destructively probing the molecular architecture of whole plant leaves. We have measured the chiroptical evolution of Hedera helix leaves for a period of 22 days. Spectrally resolved circular polarization measurements (450-900 nm) on whole leaves in transmission exhibit a strong decrease in the polarization signal over time after plucking, which we accredit to the deterioration of chiral macro-aggregates. Chlorophyll a levels measured over the same period by means of UV–vis absorption and fluorescence spectroscopy showed a much smaller decrease. With these results we are able to distinguish healthy from deteriorating leaves. Hereby we indicate the potency of circular polarization spectroscopy on whole and intact leaves as a nondestructive tool for structural and plant stress assessment. Additionally, we underline the establishment of circular polarization signals as remotely accessible means of detecting the presence of extraterrestrial life. Abstract : Highlights: Fast and sensitive circular polarization measurements through spectral multiplexing using ferroliquid crystal modulation. Spectrally resolved circular polarization measurements on intact leaves show a strong decrease in signal over time. Signal decrease cannot be described by chlorophyll a concentrations alone.